THE SYSTEM OF PUBLIC EDUCATION IN UZBEKISTAN IN THE FIRST YEARS OF INDEPENDENCE - Mustafaeva Nodira Abdullayevna (Researchparks Publishing, 2021)
This scientific article focuses on the establishment of the education system of Uzbekistan during the years of independence and its social problems and the historical way of solving them. The data were based on scientific literature, archival documents and periodicals.